After autonomy: the zapatistas, insurgent indigeneity, and decolonization. (1st October 2016) - Forbis, Melissa M.
ABSTRACT: In 2014, the Zapatistas (EZLN) celebrated the twentieth anniversary of their 1 January uprising in Chiapas against the Mexican state and the imposition of the North American Free Trade Agreement. The uprising took place in the aftermath of an upswing in hemispheric indigenous organizing around the quincentennial anniversary of the conquest of the Americas, and the 1992 constitutional recognition of Mexico as a 'pluricultural' nation. From the beginning, the Zapatistas rejected this recognition as purely symbolic, and instead demanded collective rights and resources. They also refused to see their demands as local, linking historic issues of dispossession and racism to contemporary global capitalism, while opening a space for transnational solidarity with other social and revolutionary movements. For over two decades, the Zapatistas have built a project of autonomy with the formation of autonomous municipalities, which they later consolidated into a system of territorial governance. Alongside these changes have been a global rise and interest in theories and practices of decolonization, and a questioning of the politics of national and transnational solidarity. Can Zapatista autonomy be understood as a practice of decolonization? This essay draws on longitudinal community work and ethnographic research conducted since 1994, and examines the Zapatistas' construction of an insurgent indigenous identity, attempts to regulate the boundaries of what it means to be 'indigenous', and emerging new geographies of belonging in order to open a conversation about what their modes and strategies of political organizing may offer, particularly to struggles in settler colonial states.